Women with breast cancer: perceived social support and self-care - Schneider Hermel, Júlia (2015)
This study aimed to understand the way women diagnosed with breast cancer perceive the social support they receive and how it relates to their self-care. Four participants were selected for biographical narrative interviews: two possessed high levels of social support and two possessed low levels. Axes were created to reflect the content of the interviews, such as history of the illness and the beginning of care, self-care as empowerment and as a way of looking at one’s self, care, and social support. Findings suggest that a diagnosis of breast cancer plays a key role in the development of self-care despite the obvious health risks and fragile support networks.